Blood fury : Black Dagger legacy - Ward, J. R., 1969- (Ward, J. R., 1969- Black dagger legacy., 2018)
"Brothers at the Black Dagger Brotherhood training center push recruits to the limit to become faster and stronger than ever before as they continue preparing for the fight against the lessening society. Novo, a resilient survivor and a bit rough around the edges, has overcome a great deal, including her intense attraction to suave, aristocratic Peyton. The two fighters shared a passionate physical connection. But when Peyton finally comes to terms with and admits his true feelings for Novo she rejects him for a more stable male. Now they must train in close quarters and eventually confront the feelings they still undoubtedly harbor for one another"--